The Lost Language of Democracy: Anti-rhetorical Traits in Research on Democratisation and the Interwar Crisis of Democracy - Kurunmäki, Jussi (Res Publica. Revista de Historia de las Ideas Políticas, 2015)
The article points out that the concept of democracy as used by people at large has been ignored in the research on democratisation and interwar democracy. It also shows some of the ways in which the rhetoric of democracy has been sidestepped, discussing some structuralist and other preconditionalist accounts in which the focus has been on the questions of modernisation and legitimacy as well as on political culture and ideological traditions. The article shows, furthermore, that studies of democratic transition have displayed some interest in the rhetorical aspect of politics, although this potential has not been fully played out. The article points out the difficulty of doing comparative research on the language of democracy, but nevertheless calls for a rhetorical perspective to the study of democracy.